Human rights and police - Silva, Rosimeri Aquino da (2009)
The problems in the Brazilian public safety were never as evident as today. Announced, televised, (made/turned into a show), discussed, investigated and criticized, they on the agenda of the sociologists, anthropologists, criminologists, specialists in public safety and other sections of the civil society that, every time, express their dissatisfaction with the work of our police. The theme is thorny, controversial, but captivating. We include ourselves among the so many ones unhappy with our police contributing here to the qualification of these discussions with some topics of our experience as educators in updating courses and of police formation. We were inspired by the ideas of Foucault around the problem of the power and of the violence and about the historical formation of the capitalist societies for us to think the problems about the public safety. We propose a change in the habitus of the police institutions, taking them away from their/removing them from their stratified and nested spaces, understanding, this way, the formation and the updating as privileged places of changes. Key words: Human rights; Education; Police work; Formation and police updating